2007
DOI: 10.1590/s1678-91992007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Mycobacterium bovis-AN5 infection in genetically selected mice (selection IV-A)

Abstract: Mice genetically selected for high (H) and low (L) antibody production (Selection IV-A) were used as murine experimental model. The aim of the present work was to evaluate the macrophagic activity and to characterize the immune response in Mycobacterium bovis-AN5 infected mice (3X10(7) bacteria). The response profile previously observed in such strains was not similar to that obtained during M. bovis infection; however, it corroborated works carried out using Selection I, which is very similar to Selection IV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In brief, established mouse lines, genetically selected using the immunological phenotype, efficiently produce antibodies, even when there is no immunological memory of the antigen (Magnusson et al . 1997; Cavaleiro et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, established mouse lines, genetically selected using the immunological phenotype, efficiently produce antibodies, even when there is no immunological memory of the antigen (Magnusson et al . 1997; Cavaleiro et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interaction between the immune response and the mycobacteria at the local lesion is determining the outcome of the disease. It can also be observed that granuloma protect the mycobacteria from the immune response and is probably responsible for the persistent infection ( 25 , 26 ). Microscopically, bTB granulomas have been classified into four different stages; stage I being the least severe stage while stage IV being the most severe stage ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%